Risk of air and surface contamination of SARS-CoV-2 in isolation wards and its relationship with patient and environmental characteristics - Kailu Wang; Kin-Fai Ho; Larry Yung-Tim Leung; Kai-Ming Chow; Yuk-Yam Cheung; Dominic Tsang; Raymond Wai-Man Lai; Richard Huan Xu; Eng-Kiong Yeoh; Chi-Tim Hung (Ecotoxicology and Environmental Safety, 2022)
Air and surface contamination of the SARS-CoV-2 have been reported by multiple studies. However, the evidence is limited for the change of environmental contamination of this virus in the surrounding of patients with COVID-19 at different time points during the course of disease and under different conditions of the patients. Therefore, this study aims to understand the risk factors associated with the appearance of SARS-CoV-2 through the period when the patients were staying in the isolation wards. In this study, COVID-19 patients admitted to the isolation wards were followed up for up to 10 days for daily collection of air and surface samples in their surroundings. The positivity rate of the environmental samples at different locations was plotted, and multiple multi-level mixed-effect logistic regressions were used to examine the association between the positivity of environmental samples and their daily health conditions and environmental factors. It found 6.6 % of surface samples (133/2031 samples) and 2.1 % of air samples (22/1075 samples) were positive, and the positivity rate reached to peak during 2–3 days after admission to the ward. The virus was more likely to present at bedrail, patients’ personal items and medical equipment, while less likely to be detected in the air outside the range of 2 m from the patients. It also revealed that higher positivity rate is associated with lower environmental temperature, fever and cough at the day of sampling, lower Ct values of latest test for respiratory tract samples, and pre-existing respiratory or cardiovascular conditions. The finding can be used to guide the hospital infection control strategies by identifying high-risk areas and patients. Extra personal hygiene precautions and equipment for continuously environmental disinfection can be used for these high-risk areas and patients to reduce the risk of hospital infection.